Absorption rate of subcutaneously infused fluid in ill multimorbid older patients. - Mathias Brix Danielsen; Lars Jødal; Johannes Riis; Jesper Scott Karmisholt; Óskar Valdórsson; Martin Gronbech Jørgensen; Stig Andersen (PLoS ONE, 2022)
Background Subcutaneous (SC) hydration is a valuable method for treating dehydration in the very old patients. Data are absent on the absorption rate, and the availability of SC infused fluid in the circulation in this group of patients where SC hydration is particularly relevant. Methods We performed an explorative study on ill very old (range 78-84 years old) geriatric patients with comorbidities who received an SC infusion of 235 ml isotonic saline containing a technetium-99m pertechnetate tracer. The activity over the infusion site was measured using a gamma detector to assess the absorption rate from the SC space. The activity was measured initially every 5 minutes, with intervals extended gradually to 15 minutes. Activity in blood samples and the thyroid gland was measured to determine the rate of availability in the circulation. Results Six patients were included. The mean age was 81 years (SD 2.1), the number of comorbidities was 4.6 (SD 1.3), and the Tilburg frailty indicator was 3.8 (SD 2.4). When the infusion was completed after 60 minutes, 53% (95% CI 50-56%) of the infused fluid was absorbed from the SC space, with 88% (95% CI 86-90%) absorbed one hour later. The absorption rate from the SC space right after the completion of the infusion was 127 ml/h (95% CI 90-164 ml/h). The appearance of the fluid into the blood and the thyroid gland verified the transfer from SC to circulation. Conclusion This first explorative study of absorption of SC infused fluid in the very old found an acceptable amount of fluid absorbed from the SC space into the circulation one hour after infusion had ended. Results are uniform but should be interpreted cautiously due to the low sample size. Trial registration ClinicalTrials.gov Identifier: NCT04536324.